2018
DOI: 10.1016/j.jgeb.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration, developmental pattern and genetic fidelity of somatic embryogenesis derived Musa spp.

Abstract: Multiplication of banana cvs. Grand Naine (Musa AAA, Cavendish-sub group) and Rasthali (Musa AAB, Silk-sub group) were attempted through somatic embryogenesis. The influence of position of male flower buds, amino acid supplements in the induction of somatic embryogenesis and field performance of embryogenic cell suspension (ECS) derived banana plants were studied. Differentiated immature male flower buds positioned at 6–8 th bract whorl as explants showed better callus induction and somatic embryogenesis. Supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…It was reported earlier that a very high concentration of gelling agent resulted in high water stress which led to the difficulty of uptaking water and nutrient from culture medium [4]. Many authors reported the influence of gelling agents on the development of adventitious shoots, calli [13,14], somatic embryos [2,3,15], and protoplasts [16] under in vitro culture. These studies showed that the both type and quality of gelling agents also create problems related with hyperhydricity and necrosis of the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported earlier that a very high concentration of gelling agent resulted in high water stress which led to the difficulty of uptaking water and nutrient from culture medium [4]. Many authors reported the influence of gelling agents on the development of adventitious shoots, calli [13,14], somatic embryos [2,3,15], and protoplasts [16] under in vitro culture. These studies showed that the both type and quality of gelling agents also create problems related with hyperhydricity and necrosis of the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…However, the recognition of phenotypic characteristics and diagnosis of dwarfism can only be achieved by trained personnel at the end of the greenhouse acclimatization phase or in the field [8]. Molecular techniques such as random amplified polymorphic DNA (RAPD) [7,[16][17][18] amplified fragment length polymorphisms (AFLPs) [19] and inter simple sequence repeats (ISSRs) [17,[20][21][22][23] have been proposed to monitor SV in Musa. However, the relationship among the proposed molecular markers and the SVs was not described.…”
Section: Introductionmentioning
confidence: 99%
“…Propagation through conventional methods using suckers is easy but takes longer duration for the largescale production of planting material and further they serve as the potential source of transmission of fungal pathogens, nematodes, weevils, and viruses etc. (Nandhakumar et al 2018). Therefore, the present study aimed at the rapid production of uniform and healthy planting material through development of a species-speci c protocol using shoot tip explants.…”
Section: Introductionmentioning
confidence: 99%
“…Male owers are orange yellow in colour, 2-3 cm long, 6-10 owers per bract and bi-seriate (Uma et al 2014). Most of the Rhodochlamys members are immune to Sigatoka leaf spot and Fusarium wilt diseases (Nandhakumar et al 2018).…”
Section: Introductionmentioning
confidence: 99%